Language Policy in Indonesian Islamic Boarding Schools (Pondok Pesantren): Implementation, Challenges and Impacts - Ade Christanty Yudha Bestari; Jafar Paramboor; Dinar Faiza; Meilina Haris Mayekti (Cakrawala : Jurnal Kajian Manajemen Pendidikan Islam dan Studi Sosial, 2026)
In Indonesia’s multilingual education landscape, Islamic boarding schools (pondok pesantren) play a pivotal role in shaping students’ religious and linguistic identities through bilingual language policies. While pesantren have historically emphasized Arabic for religious instruction, the inclusion of English reflects a growing need for global engagement. This study investigates the implementation, challenges, and impacts of language policies in three pesantren in Central Java. Adopting a qualitative case study approach, data were collected through semi-structured interviews, observation, and document analysis with coordinators (pak kyai/bu nyai), instructors (ustadz/ustadzah), and students (santri). This research integrates ethnographic tools particularly those oriented towards branding local wisdom activities to deepen the understanding of how pesantren construct and communicate their institutional identity through language practices. Findings revealed three distinct policy models: kitab-based instruction (pesantren 1), structured immersion (pesantren 2), and bilingual programs (pesantren 3). Challenges included limited vocabulary, low student confidence, policy-practice gaps, and insufficient interaction with native speakers. Nevertheless, bilingual policies fostered increased student confidence, enhanced public speaking skills, and multilayered linguistic identities grounded in both Islamic and global contexts. These findings highlight that effective language policy must align with institutional ideology, ensure consistent implementation, and provide authentic language exposure. It is recommended that pesantren leaders strengthen peer-based language zones, enhance teacher training in bilingual pedagogy, and explore digital platforms to connect students with native speakers. Future research should examine pesantren across other regions and investigate the long-term effects of bilingualism on students' academic and spiritual development.